O emprego formal na indústria de transformação e a relação com o índice FIRJAN de desenvolvimento para o estado do Paraná - Brunhera, Diandra Carla Uncini (2016)
According to some models of development for an economy to be considered developed it must have significant involvement of industry in its economic activity. When arose in Europe in the eighteenth century, the activity becomes essential generating higher productivity, capital accumulation and numbers of jobs, contributing to greater income generation, a key factor in promoting socioeconomic development. Besides income, other also important factor in determining the development is the level of education, this in turn seeks to alter income levels thus changing the living conditions of workers due to the classification of hand labor. It is been believed that with the industrialization workers have been qualified better to operate machines and carry out the activities of each sector more efficiently. For this study it will be considered the twelve sub-sectors of the manufacturing industry in order to check if any in particular stands out in terms of development promotion. Thus, the aim of this study is to analyze if the industrial formal employment is relating with the FIRJAN index of the state of Paraná development from 2006 to 2011. The search takes a quantitative approach, using the statistical procedure called regression with panel data and exploratory spatial analysis in order to identify trends, patterns and relationships of data. The present study provides evidence that the manufacturing sector positively influences the development index of the State of Paraná municipalities. However, to disaggregate it in the 12 subsectors that form, there is statistical significance only five, and one of them, the rubber has a negative relationship with the development during the study period. It is been observed that what seems to matter most during the development process is the degree to which people have jobs and the level of education, not just the composition of jobs in the region. Considering the results, we see the need for the search for innovation, expansion of productivity and exploitation of entrepreneurial activities grounded in education and skills of workers. The results confirm the Myrdal's theory that emphasizes the role of industry in the development process, as a factor that positively affects the standard of living of the population because of its ability to affect the purchasing power, income, demand, investment and production. It is understood that to develop a region not just one sector have employees with educational level and above average wages and employ few workers, or employ many workers with very low education level and low-paying, work needs to change the regional opportunities differences and wages that affect the development of the locality.